Webcams and Social Interaction During Online Classes: Identity Work, Presentation of Self, and Well-Being - Hosszu, Alexandra; Rughiniş, Cosima; Rughiniş, Răzvan; Rosner, Daniel (Frontiers in Psychology, 2022)
The well-being of children and young people has been affected by the COVID-19 pandemic. The shift to online education disrupted daily rhythms, transformed learning opportunities, and redefined social connections with peers and teachers. We here present a qualitative content analysis of responses to open-ended questions in a large-scale survey of teachers and students in Romania. We explore how their well-being has been impacted by online education through (1) overflow effects of the sudden move to online classes; (2) identity work at the individual and group levels; and (3) students’ and teachers’ presentations of self in the online environment, with a focus on problematic aspects of webcam use. The results indicate that both students and teachers experienced ambivalence and diverse changes in well-being, generated by the flexibility, burdens, and disruptions of school-from-home. The identities associated with the roles of teacher and student have been challenged and opened for re-negotiation. Novel patterns have emerged in teachers’ and students’ identity work. Failure or success at the presentation of self in online situations is relevant for the emotional valence of learning encounters, impacting well-being. Online classes have brought about new ways to control one’s presentation of self while also eliminating previous tactics and resources. The controversy regarding webcams has captured this duality: for some, the home remained a backstage that could not be safely exposed; for others, the home became a convenient front stage for school. Well-being was affected by the success of individual and collective performances, and by student-teacher asymmetries. Overall, our study of online learning indicates powerful yet variable influences on subjective well-being, which are related to overflow effects, identity work, and presentation of self.